PINJAMAN BERGULIR, KREDIT MACET SERTA EFEK MODERASI PENDAMPINGAN - Andri Yuni Astuti (UPAJIWA DEWANTARA: Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2017)
This study aims to determine the Revolving Loans and Non-Performing Loans (NPL) its impact on Profit Unit of the Community Self-Supporting Institutions Bangunkerto village, Sleman, Yogyakarta, with Mentoring as its moderating effect. The method used in this research is descriptive analysis and inferential analysis. Data collection in the form of a questionnaire for primary data, and Revolving Loans and NPL Reports for secondary data. Subject of primary data in this study was manager of Community Self-Supporting Institutions. Structural Equation Modeling based variance using in this research with SmartPLS application version 3.2.3. The results of this study indicate that the Revolving Loans significant positive effect on Profit Unit with a coefficient parameter of 0.476 andÂ Â Â Â  Â P-Value 0.000 <ï¡= 0.05, NPL is not proven effect on the variable Profit Unit, NPL is not proven effect on Revolving Loans, Mentoring does not affect to the profit unit, NPL with moderating effects Mentoring negatively affect on Profit Unit with a coefficient parameter of -0.306 and P-Value of 0,013 < = 0.05. Â Keywords: Revolving Loans, Non-Performing Loans, Profit Unit, Mentoring.